Strategy to Revive Bandung Skywalk; Refunctional Concept of Failed City Area - Nurcahya, Yan; Syah, M Kautsar Thariq; Sugiarto, Deri; Negara, Teddiansyah Nata; Putra, Rian Ananda; Hilmayani, Syalwa Linda (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to provide insights and recommendations for the government, the public, and future researchers in an effort to revitalize the Bandung Skywalk as a functional and effective public space. Built in 2017 as an urban tourism icon, the Bandung Skywalk experienced a decline in functionality following the Covid-19 pandemic, which restricted public activities in public spaces. This study used a qualitative descriptive method with a phenomenological approach supported by urban spatial atmosphere theory to understand users' perceptions and experiences of the space. The results indicate that the Skywalk has strategic potential for revitalization through the concept of refunctionalizing public spaces, such as developing it into a thematic tourism area or a multifunctional facility that supports residents' social and economic activities. These findings emphasize the importance of design innovation and public space management policies post-pandemic. Implicatively, this study can serve as a reference for the Bandung City Government in planning more adaptive and sustainable urban development. The research's originality lies in the integrative idea between spatial atmosphere theory and the practice of urban space revitalization, which has not been widely applied in the context of urban studies in Indonesia.